Evaluation of the Role of Community Health Center Policies in the Handling and Prevention of Tuberculosis in Malang City - Afifa, Faisa; Sholihah, Qomariyatus; Kartikaningsih, Hartati (Wacana Journal of Social and Humanity Studies, 2025)
Tuberculosis (TB) remains a significant public health issue in Indonesia, including in Malang City. Despite various strategies, the disease poses significant challenges due to social, economic, and environmental factors. This study aims to evaluate the role of Community Health Center (Puskesmas) policies in TB management and prevention efforts in Malang City while identifying factors that influence program success. A descriptive quantitative method was employed, utilizing Structural Equation Modeling (SEM), SWOT analysis, and the Analytic Hierarchy Process (AHP). Primary data were collected through questionnaires and interviews with TB patients, health workers, and the community, while secondary data were obtained from local health office reports. The findings revealed that implementing Puskesmas policies has generally been effective, particularly regarding mandatory reporting, active case finding, and free TB treatment. However, several barriers persist, including inconsistent treatment adherence, stigma surrounding TB, inadequate living conditions, and limited healthcare access in certain areas. SEM analysis identified key factors affecting TB control success: patient knowledge, environmental conditions, treatment experience, and the role of health workers. SWOT analysis highlighted strengths such as strong community engagement and policy frameworks, alongside weaknesses like insufficient environmental interventions and healthcare resource limitations. Optimization strategies proposed include enhancing public education on TB prevention, improving the home environment to support recovery, strengthening health worker capacity, integrating digital technologies, and fostering multi-sector collaboration. The study emphasizes the need to address biomedical and socio-environmental determinants for effective TB control. These findings provide strategic recommendations for enhancing Puskesmas policy implementation toward Indonesia’s 2030 TB elimination goals. Keywords: tuberculosis, community health center policy, environmental factors, public knowledge, strategy optimization